Molecular Mechanism of Cholerae Toxin (ctx) in Causing Diarrhea - Rian Ka Praja; Reny Rosalina (Denta Journal Kedokteran Gigi, 2018)
Vibrio cholerae is one of the pathogenic bacteria transmitted through contaminated food, especially contaminated seafood and beverages. V. cholerae produces cholerae toxin (ctx) which is encoded by the ctx gene located within its chromosome. This toxin has been recognized as one of the toxins responsible for cholera outbreaks. The mechanism of ctx gene expression is induced by environmental signals such as pH, osmolarity, temperature, bile, amino acids, and CO2. These signals will be a positive transcriptional factor to the ToxR gene that regulates the biogenesis of cholerae toxin. After cholerae toxin has been successfully expressed, V. cholerae uses a type II secretion (T2S) pathway to deliver cholerae toxin to the extracellular environment. Cholerae toxin consists of A and B subunits. The B subunit plays a role in attaching to the receptor Manosialosyl Ganglioside (GM1 ganglioside) and the Asubunit plays a role in catalyzing ADP-ribosylation of Gs (stimulatory) protein and turning them into active condition. The Gs protein will convert the inactive adenilate cyclase (AC) into active AC. The increase of AC activity will increase the cyclic adenosine 3'5'-monophosphate (cAMP) concentration along the cell membrane. The cAMP then causes theactive secretion of sodium (Na+), chloride (Cl-), potassium (K+), bicarbonate (HCO3-), and water (H2O) out of the cell into the intestinal lumen, resulting in large fluid losses and electrolyte imbalances.